El juego infantil y la socialización en los niños de primero de Educación General Básica de la Unidad Educativa " DR. Ricardo Cornejo Rosales". - Quishpe Alvarez, Pamela Margoth (2021)
This research was aimed at generating a proposal that was based on the importance of Childhood Play in the Socialization of First-year children of Basic General Education of the Dr. Ricardo Cornejo Rosales Educational Unit of the Guamaní parish of the city of Quito, the priority was to enhance their creativity and motor development through strategies and activities that allow them to interact and communicate through games and imaginative skills of the children in question, considering that it is a requirement for optimal growth. The Playful Strategies Guide favored the improvement of socialization in children, aimed at teachers because it is an instrument of scientific novelty, since it guide was oriented the teacher to work in a more dynamic way, using methods to develop individual and group learning, which enable the learner to promote the process of learning to learn, where the teacher is the facilitator of learning. The research was seek to demonstrate the importance of improving socialization in children as a basis for the effective advancement of a healthy coexistence, this allows starting from a diagnosis that identifies and characterizes the investigated problem, for the organization and selection of contents that make up the Guide, supported by the results of the diagnosis. The methodology was based on the applied qualitative educational approach, the techniques used were the Observation Guides and Questionnaires to measure the work performed by the teachers. This will allow to determine the methods to be used with the teachers developing the teaching-learning process, in order to make improvements from the design of the proposal. For the development of the guides, existing methods will be considered, using the methodology that responds to the needs and requirements of the boys, girls and teachers.